Las variables del comportamiento organizacional que afectan a los cambios de procesos operativos. Caso Aguiar Resistencia SA - Galizzi, Gastón (Ediciones UNL. Secretaría de Extensión de la UNL, 2019)
The object of study of this research has been the variables of the organisational behaviour that affect the changes in the operating processes.The aim of this work has been to organise the variables of organisational behaviour which affect the changes in the operating processes of Aguiar Resistencia S.A. hierarchically. The approach has been quantitative and, regarding its object of study, it has been descriptive. It is also a disciplinary, bibliographic-field and cross-sectional work. Moreover, data has been collected from semi-structured interviews and observation.As a conclusion, and illustrating the variables of the organisational behaviour affecting the operating process in the Logistics Department of Aguiar Resistencia S.A. with a pyramid, shared values are located at the bottom of the pyramid, while skills, knowledge and attitudes are placed on the next level up, followed by motivation at the penultimate level, and trust among partners is at the top.